Study of the Interference Affecting the Performance of the Theremin - Carmen Bachiller Martín; Jorge Sastre Martínez; Amelia Ricchiuti; Héctor Esteban González; Carlos Hernández Franco (International Journal of Antennas and Propagation)
The theremin is one of the earliest electronic musical instruments. It is named after the Russian physics Professor Lev S. Termen who invented it in 1919. This musical instrument belongs to a very short list of devices which are played without physical contact between the musician and the instrument. theremin players complain about the interference that any object in a radius of approximately 3 meters produces when playing the theremin, modifying the intonation of the instrument. This is a problem when playing in small scenarios, with other musicians which move around it. With the aim of reducing the degree of interference from nearby obstacles, some metallic isolating bars conforming an antenna array can be placed around the theremin pitch antenna. The paper shows different simulations calculated with the commercial software Ansoft HFSS, a tool which allows three-dimensional full wave electromagnetic field simulation, with radio frequencies, millimeter and micro waves, and experimental measures, both showing a reduction in the effect of the interference.